IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA DI BINA ANAK SHOLEH (BIAS) BOARDING SCHOOL YOGYAKARTA - Citraningsih, Diningrum; Adzkiyya Dzikrina, Nuha (An-Nadzir : Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to determine the application of human resource management in BIAS Yogyakarta Junior and Senior High School, especially in the realm of boarding schools or Islamic boarding schools. This type of research is a field study using observation, interview, and documentation techniques. The results of the study can be seen that in the implementation of human resources carried out, HR planning is carried out by the HR management bureau by analyzing report data from school principals and cottages. Second, HR recruitment is carried out in steps including determining vacant positions, determining position requirements, and determining recruitment sources and methods. Third, the selection process for job applicants is carried out by the stages of receiving a cover letter and organizing selection tests (administration and interview). Fourth, the placement of human resources in BIAS boarding school junior and senior high schools by the intended work, knowledge, abilities, skills, and expertise possessed and mastered. Fifth, training and human resource development. Sixth, compensation and provision of incentives.